PENYULUHAN /PENGENDALIAN WABAH TANPA VAKSIN CA. SERVIKS BAGI PERSONIL POLRI/PNS DAN KELUARGA OLEH BIDDOKKES POLDA SUMBAR KESEHATAN DIGITAL - Pimadella Fegita; Chandra Adilla (Nusantara Hasana Journal, 2026)
In the era of digital health, a major challenge arises regarding the spread of misinformation about disease prevention. This counseling session, themed "Cervical Cancer Outbreak Control Without Vaccines" for Indonesian National Police (Polri) personnel, civil servants (PNS), and their families, organized by Biddokkes Polda Sumbar, aims to improve health literacy through myth-and-fact-based education. The activity was conducted using interactive seminars, group discussions, and educational quizzes that encouraged active participant engagement. The results demonstrated an increase in understanding of how to distinguish between valid information and hoaxes, particularly regarding the prevention of cervical cancer without vaccines. This effort is expected to empower Polri personnel, civil servants, and their families to act as agents of change in combating health hoaxes within their environments.